2010
DOI: 10.1159/000322334
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of NO Inhibition in Renal Epithelial and Endothelial Cells in Mono-Culture vs. Co-Culture Conditions

Abstract: Nitric oxide (NO) plays a critical role in the regulation of renal hemodynamics and tubular function after post-ischemic damage or sepsis. Diminished NO bioavailability contributes to endothelial dysfunction and may be caused by reduced NO synthesis due to substrate or co-factor deficiency. The aim of this study was to investigate the effects of NOS inhibition and NO depletion in a renal endo-epithelial bilayer model compared to monolayers of proximal tubular epithelial (HK-2) cells and endothelial cells of ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
1
1
0
1
Order By: Relevance
“…In line with our results, Bertocchi et al have shown that under coculture conditions interrelation between epithelial and endothelial cells appears to counteract the potentially harmful effects of epithelial NOS inhibition [ 47 ]. Nevertheless, Gomez et al have demonstrated that Stx2 caused an oxidative imbalance in an in vivo model.…”
Section: Discussionsupporting
confidence: 92%
“…In line with our results, Bertocchi et al have shown that under coculture conditions interrelation between epithelial and endothelial cells appears to counteract the potentially harmful effects of epithelial NOS inhibition [ 47 ]. Nevertheless, Gomez et al have demonstrated that Stx2 caused an oxidative imbalance in an in vivo model.…”
Section: Discussionsupporting
confidence: 92%
“…Our studies have previously demonstrated that AAs induce oxidative stress in endothelial cells [10]. Excessive production of reactive oxygen species (ROS) may contribute to decreased nitric oxide (NO) bioavailability, leading to endothelial dysfunction and apoptosis or necrosis [11,12]. Moreover, Yang et al demonstrated that the protein expression of endothelial nitric oxide synthase (eNOS) was reduced by AAs in a mouse model of AAN [13].…”
Section: Introductionmentioning
confidence: 94%
“…Unabhängig der durchgeführten Operationen konnte auch innerhalb des renalen Systems ein bestehender Einfluss des NO auf dessen Funktion nachgewiesen werden (Bertocchi et al 2010, Kon et al 1990…”
Section: No-wirkung Und Das Herz-kreislaufsystemunclassified